2016
DOI: 10.1016/j.jfs.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of legal institutions on IPO survival: A global perspective

Abstract: Around the world, investors, practitioners, regulators and policy makers seek to understand whether, when and why recently listed stocks, initial public offerings (IPOs) are delisted rather than continue trading (survive). Using data on 7,627 IPOs issued during 2000-2008 across 32 countries, we explore the impact of the legal system on IPO survival. We find that IPOs in countries with better investor protections remain listed for longer. This suggests that better legal systems increase the net benefits compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 59 publications
3
40
3
2
Order By: Relevance
“…It can be observed from the table that the survival rate of Malaysian IPO drops to 98% after three years and 92.3% after five years following the first trading day. These findings are comparable to the recent findings in the study conducted by Espenlaub et al (2016), who examined the survival rate of the IPOs listed during 2000-2008 in four different regions including North America, Europe, BRICS, and the Asia-pacific. In comparison, the five years post-IPO survival rates (92.3%) found in this study is noticeably higher than those found in North America (73.11%), Europe (61.03%), and BRICS (81.61%), but slightly lower than Asia-pacific (93.17%).…”
Section: Kaplan-meier Survival Ratessupporting
confidence: 90%
See 2 more Smart Citations
“…It can be observed from the table that the survival rate of Malaysian IPO drops to 98% after three years and 92.3% after five years following the first trading day. These findings are comparable to the recent findings in the study conducted by Espenlaub et al (2016), who examined the survival rate of the IPOs listed during 2000-2008 in four different regions including North America, Europe, BRICS, and the Asia-pacific. In comparison, the five years post-IPO survival rates (92.3%) found in this study is noticeably higher than those found in North America (73.11%), Europe (61.03%), and BRICS (81.61%), but slightly lower than Asia-pacific (93.17%).…”
Section: Kaplan-meier Survival Ratessupporting
confidence: 90%
“…These include the transfer to another market, failure to maintain the listing requirements, unsatisfactory financial conditions as well as merger and acquisition. However, an IPO that is delisted due to transfer to another market is excluded from the definition of failure which is consistent with Espenlaub et al (2016) who defined survival as companies that continue to trade on the stock market or transfer to another stock market. Thus, only four reasons are considered in this analysis.…”
Section: Obs Ace Market -Cumulative Survival Rates (%)mentioning
confidence: 78%
See 1 more Smart Citation
“…Sudah ada banyak penelitian serupa yang dilakukan di berbagai negara diantaranya adalah di Afrika Selatan oleh Neneh & Smit (2014), di Taiwan oleh Woody et al (2013) dan , di Italia oleh Cirillo et al (2017), di Inggris oleh Espenlaub et al (2015), dan bahkan dengan cakupan global di 32 negara oleh Espenlaub et al (2016). Perlu dilakukan penelitian di Indonesia guna membuktikan terjadinya konsep tersebut pada kondisi pasar saham yang berbeda-beda.…”
Section: Latar Belakangunclassified
“…c. Profitabilitas signifikan positif mempengaruhi post-IPO survival. Hasil ini sejalan dengan penelitian Espenlaub et al (2016) yang menyatakan profitabilitas berpengaruh signifikan terhadap IPO survival. Demikian juga dengan penelitian Neneh and Smit (2014) yang menyatakan bahwa profitability ratio berpengaruh signifikan terhadap IPO survival.…”
Section: Pembahasanunclassified